Pengelolaan Kelas oleh Guru - Yusi Srihartini; Nia Trisnawati; Yuli Purwaningsih (Ikatan Dai Indonesia, 2025)
Classroom management is a fundamental competency that educators must possess to create, maintain, and restore a conducive classroom environment that facilitates the learning process. As professional educators, teachers are expected to establish and sustain an optimal learning atmosphere that supports the attainment of instructional objectives. Classroom management encompasses a series of deliberate and strategic actions undertaken by teachers to cultivate an effective learning environment. This includes fostering constructive communication and reciprocal interpersonal relationships between teachers and students, thereby promoting a harmonious and supportive classroom climate. The primary objective of classroom management is to establish a learning environment that is both effective and engaging, capable of stimulating students’ motivation to learn in accordance with their individual capacities. Furthermore, classroom management aims to eliminate various obstacles that may hinder the learning process, thereby enhancing instructional effectiveness. Consequently, the role of the teacher extends beyond the mere transmission of knowledge; it also involves motivating, supporting, and facilitating student learning. Teachers are expected to guide students to become more actively engaged in their own learning while also fostering the internalization of ethical values in daily life. A teacher is considered successful when they are able to bring about meaningful cognitive, affective, and moral development in their students.